Outcomes of hepatocellular carcinoma patients treated in the lenvatinib and immunotherapy era (2018–2021) compared to the sorafenib era (2008–2018) - Chloe A. Lim; Carla P. Amaro; Philip Q. Ding; Winson Y. Cheung; Vincent C. Tam (Cancer Medicine, 2024)
Abstract Background Lenvatinib (LEN) and atezolizumab + bevacizumab (A + B) have drastically changed the treatment paradigm for advanced hepatocellular carcinoma (HCC). Before these landmark trials, sorafenib (SOR) served as the standard first‐line treatment for a decade. Our study aimed to assess the outcomes of HCC patients treated during the SOR era (2008–2018) in contrast to those in the post‐SOR era (2018–2021), of which the predominant first‐line treatments were LEN or A + B. Methods Inclusion criteria of the study were all HCC patients in the Canadian province of Alberta who started first‐line systemic therapy at cancer centers between 1 January 2008 and 31 December 2021. Survival outcomes, including overall survival (OS) and progression‐free survival (PFS), along with clinician‐assessed response rate (RR), were subject to retrospective analysis. Results Of 372 total patients, 230 received treatment in the SOR era and 142 in the post‐SOR era. The demographic and clinical characteristics for the SOR era and post‐SOR era groups are as follows, respectively: the median age was 63 and 64 years, 80% and 81% were male, and 24% and 11% were of East Asian ethnicity. Before receiving systemic treatment, 40% and 33% received TACE, 7% and 9% received TARE, and 3% and 14% received SBRT in the two eras, respectively. In the post‐SOR era, patients received A + B (23%), LEN (51%), and SOR (23%) as first‐line treatment. There was a statistically significant improvement in RR (15% vs. 26%; p = 0.02), median PFS (3.8 months vs. 7.9 months; p < 0.0001), and median OS (9.8 months vs. 17.0 months; p < 0.0001). Conclusions In this retrospective multicenter real‐world study, HCC patients treated in the post‐SOR era, where LEN and A + B were commonly used first‐line treatments, exhibited superior OS, PFS, and RR compared to patients treated in the SOR era. The findings of this study affirm the tangible progress achieved in the real world in enhancing outcomes for HCC patients through advancements in treatments over the past 15 years.